2021
DOI: 10.33963/kp.15912
|View full text |Cite
|
Sign up to set email alerts
|

The pressure–strain work indices in response to isometric handgrip exercise

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-Non Commercial-No Derivatives 4.0 International License (CC BY-NC-ND 4.0), allowing third parties to download articles and share them with others, provided the original work is properly cited, not changed in any way, distributed under the same license, and used for noncommercial purposes only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…Therefore, it seems that the dysregulation of mechanosensing at the molecular level in various pathological conditions like hypertension leads to the loss of contractile efficiency and reduces EF-1. Along these lines, we demonstrated recently that at the peak of HG, the reduction in ejection fraction in healthy subjects is accompanied by higher myocardial work and a better work efficiency index [3]. Moreover, Faconti et al [6] showed a marked increase in EF-1 in recreational marathon runners after a race, despite the lack of increase in the conventional measure of systolic function.…”
Section: Effect Of Afterload Challenge On the First-phase Ejection Fraction And Total Ejection Fractionmentioning
confidence: 78%
See 1 more Smart Citation
“…Therefore, it seems that the dysregulation of mechanosensing at the molecular level in various pathological conditions like hypertension leads to the loss of contractile efficiency and reduces EF-1. Along these lines, we demonstrated recently that at the peak of HG, the reduction in ejection fraction in healthy subjects is accompanied by higher myocardial work and a better work efficiency index [3]. Moreover, Faconti et al [6] showed a marked increase in EF-1 in recreational marathon runners after a race, despite the lack of increase in the conventional measure of systolic function.…”
Section: Effect Of Afterload Challenge On the First-phase Ejection Fraction And Total Ejection Fractionmentioning
confidence: 78%
“…The study was performed as previously described [3]. In brief, echocardiographic tracings were acquired with a 3.5 MHz transducer (Vivid E95, GE Healthcare, Horten, Norway) at rest and at peak isometric handgrip (HG) -between 2 min 45 sec and 3 min 15 sec of maintaining 30% of maximal handgrip strength while lying in the left lateral recumbent position.…”
Section: Methodsmentioning
confidence: 99%
“…Assessing mechanical dispersion, myocardial work, isovolumetric relaxation and systolic-diastolic coupling can provide complementary information on the global and regional LV function and performance in healthy subjects. All of these parameters have demonstrated clinical value [1,[11][12][13][14][15][16][17][18][19][20]27,[32][33][34][35][36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…LV pressure-strain loops are used to assess the myocardium by several parameters. Global work efficiency (GWE) and global wasted work (GWW) are two commonly used examples [1,[13][14][15]. Myocardial work indices also quantify LV systolic function and its abnormalities and reflect global LV systolic function [1,13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation